(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Digital economy represents an effective approach to mitigate the negative economic impact of the Covid-19 pandemic. With the lack of studies related to assessing the role of the digital economy in the economic growth of countries around the world, the digital industries in Armenia, Latvia and Estonia have shown great growth potential, and the pandemic has had negative effects on digital industries in Ukraine, Egypt, Turkey and the Philippines. It proposes development strategies to bridge the "digital divide" between countries, "and enhance the driving impact of the digital economy on industrial development, employment and trade in the post-Corona era." The researcher tries to focus on increasing the Iraqi GDP by adopting the digital economy to reduce the impact of reducing OPEC+ production in the first nine months. Oil GDP, representing 61% of GDP, grew by 12.1% in 2022 despite the OPEC+ agreement In the last quarter of the year, Iraq’s rapid population growth (2.4%) also highlights a growing need for higher economic growth. The government is working to improve digital infrastructure and expand access to the Internet, and digital transformation is critical for organizations to remain viable in light of infrastructure and digital literacy challenges, strategic investments in technology and education are essential for sustainable progress and digital inclusion.